1995
DOI: 10.1002/jmr.300080604
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for and consequences of an antiviral porphyrin binding to the V3 loop of the human immunodeficiency virus (HIV‐1) envelope glycoprotein gp120

Abstract: Several porphyrin derivatives were reported to have anti-HIV-1 activity. Among them, meso-teta(4-carboxyphenyl)porphine (MTCPP) and other carboxyphenyl derivatives were the most potent inhibitors (EC50 <0.7 mu M). MTCPP bound to the HIV-1 envelope glycoprotein gp120 and to full-length V3 loop peptides corresponding to several HIV-1 isolates but not to other peptides from gp120 + gp41. However, it remained possible that MTCPP bound to regions on gp120 which cannot be mimicked by peptides. Further characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…These results showed that an important target of these compounds is the viral Env protein. Neurath et al (26,27) have correlated the anti-HIV activity by using an assay for cytotoxicity on a T-cell line that measures the inhibition of the interaction between gp120 and antibodies specific for the V3 hypervariable loop of this protein. In this series of approximately 20 porphyrins from both the natural and synthetic classes, there was no clear correlation overall between inhibition of antibody binding to gp120 and overall activity in an antiviral assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results showed that an important target of these compounds is the viral Env protein. Neurath et al (26,27) have correlated the anti-HIV activity by using an assay for cytotoxicity on a T-cell line that measures the inhibition of the interaction between gp120 and antibodies specific for the V3 hypervariable loop of this protein. In this series of approximately 20 porphyrins from both the natural and synthetic classes, there was no clear correlation overall between inhibition of antibody binding to gp120 and overall activity in an antiviral assay.…”
Section: Discussionmentioning
confidence: 99%
“…Protoporphyrin (3), hemin (22,25), and other related natural porphyrins and metalloporphyrins (11-13, 16, 25-29) have been shown to have activity against HIV in the micromolar range in such antiviral assays. Sulfonated derivatives of tetraphenylporphyrin have also been shown to be active (16,28,38) as have other selected tetra-arylporphyrins (11,15,16,(26)(27)(28). The mechanisms of action and the stage in the viral life cycle at which the porphyrins exert their inhibitory effects on HIV-1 are not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments described in Fig. 6, a full length V3loop peptide (1 mg in 0.5 mL PBS) from HIV-1 rrm gp120 (Neurath et al, 1995b) was reduced with 10 mM 2-mercaptoethanol (2-ME) for 1 h at 25°C. The reduced peptide was separated from excess 2-ME by molecular exclusion chromatography on Sephadex G-10 (Pharmacia).…”
Section: Biotinylation Of 3hp-f3-mentioning
confidence: 99%
“…Attempts to gain better understanding of the structure of the third variable domain, designated as V3 loop, of the human immunodeficiency virus (HIV-1) gp120 envelope glycoprotein, a target for anti-HIV drug discovery [12][13][14], was the principal reason for us to model disulfide bonded loops in proteins. This loop, bonded by a pair of invariant cysteines, has been shown to play an important role in virus entry into CD4+ cells and in the tropism and infectivity of HIV-1 [15].…”
mentioning
confidence: 99%